EDUKASI MEMILIH JAJANAN SEHAT BEBAS BORAKS PADA SISWA SEKOLAH DASAR INPRES KAMPUS IKIP MAKASSAR - Sulfiani, Sulfiani; Thayeb, Andi Meinar Dwi Rantisari (Nindikayla Institute, 2023)
Snack food for school children (PJAS) is snack food that is found in the school environment and is the daily consumption of school children which is eaten by students during breaks and after school. The safety of school snacks is still low and is still an important problem that needs attention. The large use of chemicals that are often used to extend the shelf life of these foods such as borax which is widely used. IKIP Campus Inpres Elementary School has a very strategic and wide location making it easier for sellers to choose that location as a place to sell their snacks. This community service aims to provide knowledge and information to students in the form of education about choosing healthy snacks free of borax. This activity was carried out at the Inpres Elementary School, IKIP Makassar Campus and the target participants were fifth grade students. The method used in this activity was in the form of lectures, discussions and mini quizzes. This activity ran smoothly because of the support from the teacher and the enthusiasm of the students in the class. The results of this activity indicate that the level of understanding of students can be seen in the discussion sessions and mini quizzes